Therapeutic cancer vaccines: From biological mechanisms and engineering to ongoing clinical trials. (September 2022) - Sobhani, Navid; Scaggiante, Bruna; Morris, Rachel; Chai, Dafei; Catalano, Martina; Tardiel-Cyril, Dana Rae; Neeli, Praveen; Roviello, Giandomenico; Mondani, Giuseppina; Li, Yong
Highlights: FDA anti-SARS-CoV-2 vaccines propel therapeutic anti-cancer vaccine platforms. Simple mRNA structure alterations in vaccines gives more engineering flexibility. Vaccines stability, antigen translation and delivery through lipid nanoparticles. Nucleic-acid, peptide, cellular, personalized neoantigen vaccines investigations. Comprehensively review of key ongoing clinical trials. Abstract: Therapeutic vaccines are currently at the forefront of medical innovation. Various endeavors have been made to develop more consolidated approaches to producing nucleic acid-based vaccines, both DNA and mRNA vaccines. These innovations have continued to propel therapeutic platforms forward, especially for mRNA vaccines, after the successes that drove emergency FDA approval of two mRNA vaccines against SARS-CoV-2. These vaccines use modified mRNAs and lipid nanoparticles to improve stability, antigen translation, and delivery by evading innate immune activation. Simple alterations of mRNA structure- such as non-replicating, modified, or self-amplifying mRNAs- can provide flexibility for future vaccine development. For protein vaccines, the use of long synthetic peptides of tumor antigens instead of short peptides has further enhanced antigen delivery success and peptide stability. Efforts to identify and target neoantigens instead of antigens shared between tumor cells and normal cells have also improved protein-based vaccines. Other approaches use inactivated patient-derived tumor cells to elicit immune responses, or purified tumor antigens are given to patient-derived dendritic cells that are activated in vitro prior to reinjection. This review will discuss recent developments in therapeutic cancer vaccines such as, mode of action and engineering new types of anticancer vaccines, in order to summarize the latest preclinical and clinical data for further discussion of ongoing clinical endeavors in the field.